2016
DOI: 10.1093/nar/gkw161
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of gyrase-mediated resistance by C7 aryl fluoroquinolones

Abstract: Fluoroquinolones form drug-topoisomerase-DNA complexes that rapidly block transcription and replication. Crystallographic and biochemical studies show that quinolone binding involves a water/metal-ion bridge between the quinolone C3-C4 keto-acid and amino acids in helix-4 of the target proteins, GyrA (gyrase) and ParC (topoisomerase IV). A recent cross-linking study revealed a second drug-binding mode in which the other end of the quinolone, the C7 ring system, interacts with GyrA. We report that addition of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In support of this idea, we recently found that an aryl group appended to the C7 piperazinyl ring of ciprofloxacin, which according to X-ray structures should extend into GyrB, suppresses the protective effect of GyrA resistance substitutions. 65 The most active example found to date is a C7 dinitrophenyl derivative of ciprofloxacin (compound 7 ), a compound that selectively enriches cells carrying an uncommon gyrA resistance mutation. To our knowledge, C7-aryl derivatives of ciprofloxacin have not been examined as potential imaging agents.…”
Section: Fluoroquinolone Actionmentioning
confidence: 99%
“…In support of this idea, we recently found that an aryl group appended to the C7 piperazinyl ring of ciprofloxacin, which according to X-ray structures should extend into GyrB, suppresses the protective effect of GyrA resistance substitutions. 65 The most active example found to date is a C7 dinitrophenyl derivative of ciprofloxacin (compound 7 ), a compound that selectively enriches cells carrying an uncommon gyrA resistance mutation. To our knowledge, C7-aryl derivatives of ciprofloxacin have not been examined as potential imaging agents.…”
Section: Fluoroquinolone Actionmentioning
confidence: 99%
“…The most common, quinolone and its derivatives like ciprofloxacin (CIP), is targeting the DNA gyrase A (GyrA) which is essential for DNA replication [8,9]. Quinolone interaction with GyrA has been well studied thanks to the 3D structure of the E.coli protein [10]. The mutation of critical sites lead to resistance; these sites are located in the so-called Quinolone Resistant-Determining Region (QRDR) [11].…”
Section: Introductionmentioning
confidence: 99%
“…A map of E.coli GyrA protein featuring structural and functional domains is shown at the bottom for comparison. The map was generated based on the following references[10,12,13]. The GyrA protein sequence of E.coli and N.meningitidis reference strain 053442 (GB-ID CP000381) were compared (AdditionalTable 4).…”
mentioning
confidence: 99%
“…The most common, quinolone and its 4 derivatives, is targeting the DNA gyrase A which is essential for DNA replication (11,12). Quinolone interaction with DNA gyrase has been well studied thanks to the 3D structure of the E.coli protein (13). The mutation of critical sites lead to resistance and they are located in the so called Quinolone Resistant-Determining Region (QRDR) (14).…”
Section: Introductionmentioning
confidence: 99%